KAJIAN YURIDIS PROGRAM PENERBITAN SERTIPIKAT HAK ATAS TANAH ELEKTRONIK - Agustina, Enny (Solusi, 2021)
This study discusses how the juridical study of the electronic land rights certificate issuance program and how the mechanism in the issuance of electronic land rights certificates. This research method is normative legal research with a statutory approach, by reviewing regulations related to legal issues. The result of this research is the juridical aspect of issuing electronic certificates is contained in the Minister of ATR/Head of BPN Regulation Number 1 of 2021. In Article 1 number 8 of the Ministerial Regulation defines electronic certificates as "Certificates issued through the Electronic System in the form of Electronic Documents". So the results of land registration activities are published in the form of electronic documents. The mechanism for issuing electronic certificates in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 1 of 2021 concerning Electronic Certificates begins with the issuance of certificates for the first time and continues with the replacement of conventional certificates with electronic certificates, although this is not mandatory, it is considered important to be applied to minimize document falsification. The conclusion in this study is that an electronic system is a necessity for today's modern era, but to ensure and not reduce the legal certainty of land rights, a comprehensive and holistic study, both juridically and technically, on electronic certificates needs to be carried out and criminal acts as if It is also developing along with the development of information technology, it is feared that there will be a risk to electronic certificates, especially forged electronic signatures, because to find out if it is falsified or not, there must be a verification of the comparison of the similarity of values between documents and electronic signatures, this is what makes the difference between electronic signatures in electronic certificates so that the risk of forgery can be detected immediately by itself.